Anticorpos anti-Leishmania spp. em felinos domésticos - Oliveira, Gabriela Capriogli [UNESP]; Paiz, Laís Moraes; Menozzi, Benedito Donizete [UNESP]; Lima, Michele de Souza; de Moraes, Carla Cristina Guimarães; Langoni, Helio [UNESP] (FapUNIFESP (SciELO), 2015)
Leishmaniasis is a vector-borne zoonotic disease caused by protozoa in the genus Leishmania, typical of rural and peri‑urban environments. The causative agent of American visceral leishmaniasis is Leishmania (Leishmania) infantum chagasi and the main insect vector in Brazil is Lutzomyia longipalpis. Dogs (Canis familiaris) are important in the transmission of the disease, as a reservoir closely related to humans and an infection source for phlebotomine vectors. Since 1990, an increasing number of feline leishmaniasis cases have been reported, suggesting that domestic cats (Felis catus) might be involved in the epidemiology of the disease. The present study analyzed the prevalence of anti-Leishmania spp. antibodies in naturally infected domestic cats from various neighborhoods in the municipality of Belém, Pará, Brazil, using the indirect immunofluorescence assay (IFA) and the direct agglutination test (DAT). Among the 443 samples tested, 18 (4.06%) presented positive reactions in the IFA. The observed titers were 40 IU in 4.97% of the samples and 80 IU in 0.90%. In the DAT test, positive results were found in 25 (5.64%) of the samples. The observed titers were also 40 IU (4.97%) and 80 IU (0.68%). The agreement rate between the two tests was considered low (Kappa coefficient = 0.10).
Antibodies to Leishmania spp. in domestic felines
Keywords: Cats; Direct agglutination test; Indirect immunofluorescence assay; Leishmaniasis